Creating Desires: The Effects of Television Toy Advertising on Children - Car, Sandra (2008)
Every day children are exposed to a wide range of toy commercials on television. Toys are presented in a way that makes them look very attractive and great fun to play with. Many studies have found that it is not until 8 years of age that children begin to understand the selling purpose of a commercial. However, cognitive development does not necessarily protect children against the effects advertising has on them. In order to explore the influence of toy commercials on older children, this paper is concerned with the students aged 8-10 and aims to examine how receptive they are to the commercial messages of toy advertisers.
Projekt MZOS
ENG